(untitled) (Global Journal of Science Frontier Research, 2020)
By using pythagorean fuzzy sets and T-S fuzzy descriptor systems, the new ()-pythagorean fuzzy descriptor systems are proposed in this paper. Their definition is given firstly, and the stability of this kind of systems is studied, the relation of ()-pythagorean fuzzy descriptor systems and T-S fuzzy descriptor systems is discussed. The ()-pythagorean fuzzy controller and the stability of ()- pythagorean fuzzy descriptor systems are deeply researched. The ()-pythagorean fuzzy descriptor systems can be better used to solve the problems of actual nonlinear control. The ()-pythagorean fuzzy descriptor systems will be a new research direction, and will become a universal method to solve practical problems. Finally, an example is given to illustrate effectiveness of the proposed method.